Development of an Enhanced Recovery After Surgery Guideline and Implementation Strategy Based on the Knowledge-to-action Cycle. Issue 6 (December 2015) - McLeod, Robin S.; Aarts, Mary-Anne; Chung, Frances; Eskicioglu, Cagla; Forbes, Shawn S.; Conn, Lesley Gotlib; McCluskey, Stuart; McKenzie, Marg; Morningstar, Beverly; Nadler, Ashley; Okrainec, Allan; Pearsall, Emily A.; et al.
Abstract : Background: Enhanced Recovery After Surgery (ERAS) protocols have been shown to increase recovery, decrease complications, and reduce length of stay. However, they are difficult to implement. Objective: To develop and implement an ERAS clinical practice guideline (CPG) at multiple hospitals. Methods: A tailored strategy based on the Knowledge-to-action (KTA) cycle was used to develop and implement an ERAS CPG at 15 academic hospitals in Canada. This included an initial audit to identify gaps and interviews to assess barriers and enablers to implementation. Implementation included development of an ERAS guideline by a multidisciplinary group, communities of practice led by multidiscipline champions (surgeons, anesthesiologists, and nurses) both provincially and locally, educational tools, and clinical pathways as well as audit and feedback. Results: The initial audit revealed there was greater than 75% compliance in only 2 of 18 CPG recommendations. Main themes identified by stakeholders were that the CPG must be based on best evidence, there must be increased communication and collaboration among perioperative team members, and patient education is essential. ERAS and Pain Management CPGs were developed by a multidisciplinary team and have been adopted at all hospitals. Preliminary data from more than 1000 patients show that the uptake of recommended interventions varies but despite this, mean length of stay has decreased with low readmission rates and adverse events. Conclusions: On the basis of short-term findings, our results suggest that a tailored implementation strategy based on the KTA cycle can be used to successfully implement an ERAS program at multiple sites.